Impaired Endothelial-Dependent and Endothelium-Independent Vasodilatation in Patients With Thromboangiitis Obliterans. (January 2013) - Brodmann, M.; Hafner, F.; Gary, T.; Seinost, G.; Pilger, E.
Background: Endothelial dysfunction is the key process in the development of atherosclerosis. The aim of our study was to evaluate endothelial dysfunction measured by the noninvasive technique of Celermajer that plays a role in the pathogenesis of thrombangitis obliterans. Methods: A total of 36 patients with thrombangitiis obliterans ([TAO]; mean age 44.9 ± 1.3 years) were compared with 30 healthy individuals (mean age 36.1 ± 1.8 years). High frequency ultrasound was used to measure changes in response to reactive hyperemia (leading to flow-mediated endothelium-dependent dilatation) and in response to 0.4 mg sublingual nitroglycerin ([NTG]; leading to NTG-induced, endothelium-independent dilatation). Results: Patients with TAO showed a lower but statistically not significant flow-mediated dilatation and a statistically significant reduced NTG-induced vasodilatation than the control group. Conclusion: Our results suggest that both mechanisms play a role in patients with TAO, the endothelium-independent impaired vasodilatation even in a more significant way than the impaired endothelium-dependent vasodilatation.